Tanggung Jawab E-Commerce Terhadap Konsumen Serta Penerapan Choice of Law dan Jurisdiction Clause dalam Transaksi Lintas Negara: Penelitian - Yohanes Christopher June; Annisa Fitria (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This research aims to examine the scope and limits of legal accountability of International e-commerce service providers towards customers in Indonesia, as well as the impact of legal and forum selection provisions in International transactions. Through a normative approach, examining the compatibility between domestic laws and regulations. For example, the Consumer Protection Law and Government Regulation Number 80 of 2019, which includes electronic standard agreements, especially those used by the Amazon platform, reveals that foreign platform providers have a legal obligation to ensure the reliability of their systems and provide accessible dispute resolution procedures. However, legal disparities were identified in Amazon’s standard contract, which unilaterally stipulates the law and jurisdiction of the United States. This provision has the potential to conflict with Article 18 of the Consumer Protection Law. It was concluded that if the clause is not in line with national consumer protection principles, it can be considered legally invalid, and therefore, dispute resolution must refer to Indonesian jurisdiction. Therefore, provisions on choice of law and jurisdiction that conflict with the Consumer Protection Law and Government Regulation Number 80 of 2019 can be declared invalid. Thus, dispute resolution should be returned to the Indonesian legal mechanism and jurisdiction to ensure legal certainty and protect consumer rights.